'Kill All The Sorcerers': The Interconnections Between Sorcery, Violence, War and Peace in Bougainville. (30th October 2018) - Forsyth, Miranda
Abstract: This paper provides new insights into how violence in war structures peacetime violence by highlighting how war alters ontological positions or worldviews, such as those concerning the relevance of threat of harm through spiritual means. It presents a detailed case study of sorcery accusations and related violence before, during and after Bougainville's decade long civil war. New empirical data are used to illustrate the mechanisms through which violence against those accused of sorcery was enabled and legitimized during the war and how this remains linked to contemporary sorcery accusations and related violence two decades after peace. Drawing on Braithwaite and D'Costa's framework of cascades of violence, the paper also tracks the ways in which sorcery discourses, practices and beliefs cascade to war.